Konsep Pendidikan Islam Anak Usia Dini Perspektif Al-Ghazali Dan Abdullah Nashih Ulwan (Studi Komparasi Pemikiran) - Alfiah, Siti (Institut Agama Islam Negeri Ponorogo, 2020)
Abstract: Education is fundamental in improving the welfare of the nation, because education is a place for moral cultivation, good character, independence, and other knowledge. Al-Ghazali is one of the leaders of classical Islamic thought who is a Sufism thinker and many of the expertise he mastered, one of which is dubbed as Hujjatul Islam (defender of Islam) and Imam al-Murabbin (Expert in Education), while Abdullah Nashih Ulwan is a figure of modern thought in in the world of education. He was the first person to introduce Tarbiyah Islamiyah subjects which were used as basic lessons in school. This study aims to determine the similarities and differences of early childhood Islamic education from the perspective of Al-Ghazali and Abdullah Nashih Ulwan. This research was conducted using a qualitative approach. This type of research is library research (library research). Data collection techniques used were using the documentation method. Data analysis techniques using content analysis techniques. The results of this study are similarities and differences in the concept of early childhood Islamic education from the perspective of Al-Ghazali and Abdullah Nashih Ulwan.